La dixi de persona en el dicurs acadèmic oral en català - Nogué Serrano, Neus (Caplletra. Revista Internacional de Filologia, 2008)
In this article the results of a quantitative and qualitative research into person deixis are shown and, generally, the ones related to the participative inscription, within the oral academic genre of the master class. In order to do so, this discursive genre has been contrasted with colloquial oral conversation and academic prose. The quantitative results include the distribution of the references to the enunciator and to the enunciatary in the three genres (the individual ones, the collective ones and those that allow the participants to avoid direct reference). From the qualitative point ofview, the main pragmatic functions that make the deictic expressions of person in the master class are described: regarding those of the enunciator, the management of the speech, the reference to the collectives in which the enunciator is included, themanagement of the process of knowledge and the textual use of the dexis; and regarding those of the second person, the attraction of the audience’s attention and their introduction to the expounded topic.